Identification of alcohol use disorders among women in the Republic of Khakassia - E. V. Fadeeva; V. I. Garder; O. I. Indinok; Y. V. Patlasova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents results of a regional project to prevent and reduce the prevalence of alcohol consumption among women in the Republic of Khakassia (Eastern Siberia, Russian Federation). In addition to the main preventive goal of reducing alcohol consumption among groups of women covered by the project, there was an objective to conduct screening using the AUDIT test and provide motivational counseling in case of identifying alcohol-related problems. 691 women took part in screening, among them 202 at enterprises of the Republic of Khakassia, and 489 when seeking social/psychological support to the Khakass Republican Branch of the Russian Red Cross, as well as to local branches of the Red Cross in other cities of the Republic of Khakassia. Levels of risk related to alcohol use were identified, based on the results of the screening the studied groups of women. Depending on the risk level, three types of socio-psychological interventions were carried out: informing about harmful consequences of alcohol use and the need to maintain a healthy lifestyle; motivational counseling; motivating women for treatment of dependency.Majority of women who were screened at workplaces were more likely to use alcohol with low risk (78.2%), much smaller proportion of women had risky alcohol consumption (14.4%), alcohol consumption with harmful consequences (2.5%) or signs of alcohol dependency (2.0%). Among women who applied for social and psychological support to branches of the Russian Red Cross, prevalence of low-risk use was lower (43.4%), and risky alcohol use (31.3%), alcohol use with harmful consequences (10.6%) or signs of alcohol dependency (14.5%) were significantly higher.